Timely Initiation of Antenatal Care and Associated Factors among Pregnant Women Attending at Wachemo University Nigist Eleni Mohammed Memorial Comprehensive Specialized Hospital, Hossana, Ethiopia: A Cross-Sectional Study - Dagmawit Tessema; Amanuel Kassu; Amanuel Teshome; Ritbano Abdo (Journal of Pregnancy)
Background. Timely detection and treatment of pregnancy-related or preexisting diseases, health education, and the promotion of adequate care provision improve the health of mothers and unborn children. As such, these factors are crucial within the first pregnancy trimester. However, very few women in low and middle-income countries initiate their first ANC in the recommended trimester of pregnancy. This study is aimed at assessing the prevalence of timely initiation of ANC and its associated factors among pregnant women attending antenatal clinics in Wachemo University Nigist Eleni Mohammed Memorial comprehensive specialized hospital, Hossana, Ethiopia. Methods. A hospital-based cross-sectional study was conducted from April 4, 2022 to May 19, 2022. A systematic sampling technique was used to select study participants. Data were collected from pregnant women using a pretested structured interview questionnaire. EpiData version 3.1 was used to enter the data, and SPSS version 24 was used to analyze it. Bivariate and multivariable logistic regression were used to identify the associated factors at a 95% confidence interval with a p value < 0.05. Results. This study indicated that 118 (34.3%) of the women initiated ANC timely. The factors associated with timely initiation of ANC included women aged 25–34 years (AOR=0.3; 95% CI: (0.1, 0.7)), tertiary maternal education (AOR=3.2, 95% CI: (1.0, 9.9)), zero parity (AOR=7.7; 95% CI: (3.6, 15.3)), planned pregnancy (AOR=13.7; 95% CI: (5.5, 34.3)), good knowledge about ANC services (AOR=3.1; 95% (CI: (2.3, 11.3)), and good knowledge about danger signs in pregnancy (AOR=4.8; 95% CI: (2.2, 8.1)). Conclusion. This study demonstrates the importance of making a significant effort to increase the coverage of timely ANC initiation in the study area. Therefore, increasing the awareness level of mothers regarding ANC services given during pregnancy and danger signs in pregnancy and advancing the academic level of mothers are essential to increase the coverage of timely initiation of ANC.